2015
DOI: 10.2147/copd.s73864
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: mindfulness meditation intervention in COPD

Abstract: Living well with chronic obstructive pulmonary disease (COPD) requires people to manage disease-related symptoms in order to participate in activities of daily living. Mindfulness practice is an intervention that has been shown to reduce symptoms of chronic disease and improve accurate symptom assessment, both of which could result in improved disease management and increased wellness for people with COPD. A randomized controlled trial was conducted to investigate an 8-week mindful meditation intervention prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 45 publications
1
35
1
3
Order By: Relevance
“…75 Mind-body exercise, such as tai chi and yoga, may be helpful to engage deconditioned patients in physical activity either as a bridge, adjunct, and/or alternative to conventional choices. 77,78 …”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…75 Mind-body exercise, such as tai chi and yoga, may be helpful to engage deconditioned patients in physical activity either as a bridge, adjunct, and/or alternative to conventional choices. 77,78 …”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Interestingly, in COPD, some have suggested that mindfulness may trigger anxiety, and that perhaps other meditation styles may be better suited. 78 In practice, however, elements of mindfulness are common to many styles, and it is unclear why patients with COPD would be different from other chronic disease populations, including asthma. In fact, studies have shown that mindfulness programs in other chronic disease populations can promote self-care, improve sleep and well-being, and increase adherence to medical recommendations.…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Studies evaluating the efficacy of a mindfulness program in individuals with a respiratory diagnosis have applied a number of outcomes including; quality of life, lung function, medication use, dyspnea, stress, anxiety and depression [7][8][9], [14]. However, the observed effects have been limited [12].…”
Section: Optimism Was Expressed Bymentioning
confidence: 99%
“…Its positive impact on fatigue, self-efficacy and quality of life has been reported in; heart failure, arthritis and asthma [5][6][7]. The lack of effect of mindfulness in individuals with COPD has been ascribed to poor adherence [8], with improvements in emotional function being observed in those who completed six or more sessions [9].…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study by Chan et al, using a similar population and similar intervention showed no significant improvement compared to control. However, for the group of patients that completed at least six sessions, there was a significant improvement in emotional function (158).…”
Section: Relaxation Therapymentioning
confidence: 91%